Rage, Outrage and Hope: A Glimpse of the Latin American Experience (2022)
This paper juxtaposes the works of the Ecuadorian painter Oswaldo Guayasamín and the Brazilian pedagogue Paulo Freire, drawing on the affective configurations of rage and hope that, in our view, they have in common. The perspective we assume in our enquiry is based on Paul Ricoeur’s understanding of hermeneutics, so it is from this perspective that we approach their works in order to ask, finally, whether the affective configurations, in which anger, indignation and hope play a preponderant role, account for a specific way of living and constituting our Latin American experience.